Trypan blue staining in the macular hole treatment - Pel-Przybyszewska, Edyta; Szkudlarek, Ewa; Szkudlarek, Anna; Nawrocki, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The purpose of the study was to estimate the results of macular hole surgery using pars plana vitrectomy, ILM peeling with and without dye-trypan blue and endotamponade. We observed that trypan blue increases the precision and safety of surgery and improves the postoperative anatomical and functional results.